Evaluación antropométrica nutricional de las voleibolistas en la escuela de talentos de Trujillo - Venezuela - León Pérez, S.; Chacón Ramos, L. M.; Carvajal Veitia, W.; Campos Bermúdez, Y. (Revista Cubana de medicina del deporte y la cultura fisica, 2019)
In players of any age they are indispensable the kinanthropometric valuations on weight, height and body composition, like part of the medical control of the training. Equally important they are those studies to follow the evolution of the physical development, as indicators of the health and of the nutritional state in young sportsmen. The objective of the present reports it is to expose and to comment the results of the nutritional evaluation carried out the female students players of Volleyball, in the School of Talents of Trujillo, Venezuela, by means of the application of three procedures based on anthropometric measurement: the of Body Mass Index (BMI), the proportion of weight to height and the estimate of the protein and caloric reservations, according to the fat and muscular area of the arm. They presents and discusses the results, the relevancy of one each of those procedures and the level of information that give to supplement the actions of the medical control in the ages of sport initiation, in order to take the dietary, prophylactic-therapeutic and pedagogic measures required in the training, particularly in the athletes that present some malnutrition form. To concludes that most of the players evaluated by three anthropometrical procedures presents a satisfactory nutritional state, inside the ranges of weight "normal" or "healthy". The Index of Corporal Mass showed smaller accuracy when estimating the nutritional state of the studied adolescent sportsmen, in comparison with the other two applied procedures, mainly in the analysis casuistically malnutrition singular for defect or for excess. The inclusion of indicative anthropometrics of the corporal composition, as the muscular and fatty areas of the arm and the senatorial of the panicles, next to the values of weight for the size, they contribute a bigger precision on the nutritional state of the studied sportsmen.